The Role of Stress and Stress Adaptations in Determining the Fate of the Bacterial Pathogen Listeria monocytogenes in the Food Chain - NicAogáin, Kerrie; O’Byrne, Conor P. (Frontiers in Microbiology, 2016)
The foodborne pathogen L. monocytogenes is a highly adaptable organism that can persist in a wide range of environmental and food-related niches. The consumption of contaminated ready-to-eat (RTE) foods can cause infections, termed listeriosis, in vulnerable humans, particularly those with weakened immune systems. Although these infections are comparatively rare they are associated with high mortality rates and therefore this pathogen has a significant impact on food safety. L. monocytogenes can adapt to and survive a wide range of stress conditions including low pH, low water activity, and low temperature, which makes it problematic for food producers who rely on these stresses for preservation. Stress tolerance in L. monocytogenes can be explained partially by the presence of the General Stress Response (GSR), a transcriptional response under the control of the alternative sigma factor sigma B (B) that reconfigures gene transcription to provide homeostatic and protective functions to cope with the stress. Within the host B also plays a key role in surviving the harsh conditions found in the gastrointestinal tract. As the infection progresses beyond the GI tract L. monocytogenes uses an intracellular infectious cycle to propagate, spread and remain protected from the host’s humoral immunity. Many of the virulence genes that facilitate this infectious cycle are under the control of a master transcriptional regulator called PrfA. In this review we consider the environmental reservoirs that enable L. monocytogenes to gain access to the food chain and discuss the stresses that the pathogen must overcome to survive and grow in these environments. The overlap that exists between stress tolerance and virulence is described. We review the principal measures that are used to control the pathogen and point to exciting new approaches that might provide improved means of control in the future.